Kecemasan dan motivasi belajar - Vivin, Vivin (Persona:Jurnal Psikologi Indonesia, 2019)
AbstractThis study aims to determine the relationship between anxiety with learning motivation and the hypothesis of this study stated that there is a negative correlation between anxiety with learning motivation, assuming the higher anxiety, the lower the learning motivation will be and conversely the lower anxiety, the higher learning motivation will be. The subject population of this study was 1.241 students, and the number of samples used was 275 students of 13th State Senior High School Medan selected by disproportionate stratified random sampling. Data were obtained from the Hamilton Anxiety Rating Scale (HARS) to measure anxiety and learning motivation scale. The analysis of the data was performed by Pearson Product Moment Correlation with SPSS 17 for Windows. The results of this research showed that there is a negative relationship between anxiety with learning motivation. Students who have no acute anxiety feelings would be able to cope with difficult learning situations with prepare through learning activities. Conversely, the students who have excessive anxiety would tend to have a negative perception that there is no motivation and passion for learning. Keywords: Anxiety; Learning motivation AbstrakPenelitian ini bertujuan untuk mengetahui hubungan antara kecemasan dengan motivasi belajar dan hipotesis yang diajukan dalam penelitian ini adalah ada hubungan negatif antara kecemasan dengan motivasi belajar, asumsinya bahwa semakin tinggi kecemasan, maka semakin rendah motivasi belajar dan sebaliknya semakin rendah kecemasan maka semakin tinggi motivasi belajar. Populasi subjek penelitian ini sebanyak 1.241 orang, dan jumlah sampel yang digunakan adalah 275 orang siswa-siswi SMA Negeri 13 Medan yang dipilih dengan metode disproportionate stratified random sampling. Data diperoleh dari Hamilton Anxiety Rating Scale (HARS) untuk mengukur kecemasan dan skala motivasi belajar. Analisis data yang digunakan adalah menggunakan korelasi Pearson Product Moment melalui bantuan SPSS 17 for Windows. Hasil penelitian ini menunjukkan bahwa ada hubungan negatif antara kecemasan dengan motivasi belajar. Siswa-siswi yang tidak memiliki perasaan cemas berlebihan, akan mampu mengatasi situasi pembelajaran yang sulit dengan mempersiapkan diri melalui kegiatan belajar. Sebaliknya siswa-siswi yang mengalami perasaan cemas berlebihan akan cenderung memiliki persepsi negatif sehingga tidak memiliki motivasi dan gairah untuk belajar. Kata kunci: Kecemasan; Motivasi belajar